Effects of Poly(propylene glycol)‐Based Triamine on the Sol/Gel Curing and Properties of Hybrid Non‐Isocyanate Polyurethanes. Issue 3 (29th January 2022) - Bowman, Louis‐Paul; Younes, Georges R.; Marić, Milan
Abstract: Non‐isocyanate polyurethanes (NIPUs) synthesized from biodiesel‐derived diglycerol dicarbonate (DGC) and triamine functional poly(propylene glycol) (Jeffamine) are investigated to improve upon poor water resistance and slow curing kinetics observed in (DGC/diamine functional Jeffamine) NIPUs. The structural, thermal, and rheological properties of the prepolymer formulations match those of their diamine‐prepared analog previously reported. The NIPU prepolymers (number average molecular weight, MN between 4200 and 6400 g mol −1 ) are subsequently functionalized with trimethoxy silane end‐cappers to yield moisture‐curable hybrid NIPUs. The prepolymers are both successfully end‐capped and subsequently cured under ambient conditions. The sol/gel curing kinetics of the prepolymers are extensively studied, and the effects of the capping methodology, moisture, and the amount of catalyst are quantified so that gel times are observed in as little as 1.4 h at room temperature. The developed curing methods are effective leading to final hybrid films with high gel contents (>86%). The tensile properties of the final films resulting are considerably better compared to previously reported DGC/Jeffamine‐based NIPUs, which are too soft to undergo mechanical testing. Also, the films are found to exhibit a tenfold decrease in water absorption compared to the latter (5% vs 70%, respectively). Abstract : Non‐isocyanate polyurethanes based on renewable diglycerol dicarbonate and poly(propylene glycol)‐based triamines are synthesized. The prepolymers are functionalized with silane cappers to yield moisture‐curable formulations. Improvements in curing kinetics and practicality of these materials are achieved as a result of increasing the amine capping sites. Physical properties of the hybrid polymers, in particular strength and water resistance, are improved.